2014
DOI: 10.18388/abp.2014_1895
|View full text |Cite
|
Sign up to set email alerts
|

The relation of PON1-L55M gene polymorphism and clinical manifestation of Behcet's disease.

Abstract: Purpose: Behçet's disease is a multisystem disease characterized by recurrent oral and genital ulcers, relapsing uveitis, mucocutaneous, articular, gastrointestinal, neurologic, and vascular manifestations. Paraoxonase is believed to play an important role in protection of LDL and HDL particles from oxidation, in antioxidant effect against lipid peroxidation on cellular membranes, and in anti-inflammatory process. Lipid peroxidation and free oxygen radicals have been thought to play a role in pathogenesis of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Both enzymes are capable to restrain LDL oxidation 34 and trigger antioxidant properties along with cholesterol efflux of HDL [35], [36]. Association of PON2 and PON3 polymorphism with various disorders has sparingly been studied [14], [15], [16], [17], [18], [19], [20], [21]. Present study was conducted to explore association between senile cataract and PON2 and PON3 polymorphism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both enzymes are capable to restrain LDL oxidation 34 and trigger antioxidant properties along with cholesterol efflux of HDL [35], [36]. Association of PON2 and PON3 polymorphism with various disorders has sparingly been studied [14], [15], [16], [17], [18], [19], [20], [21]. Present study was conducted to explore association between senile cataract and PON2 and PON3 polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Paraoxonases are calcium dependent antioxidant enzymes constituting three isoforms PON1, PON2 and PON3 10 . PON1 polymorphism has been studied in different disorders including cataract,[11], [12] diabetes, 13 age related macular degeneration, 14 Alzheimer’s disease, 15 Behcet’s disease, 16 and atherosclerosis 17 . Data for PON2 and PON3, however, is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Asefi et al (24) asserted that PON1 55 M allele is a risk factor for the psoriasis. Dursun et al (25) reported that there was a relation between PON1 55 M allele polymorphism and Behçet disease. Although there were no significant differences between the groups with respect to PON1 L55M polymorphism, Gürel et al 9 presence of increased frequency in AA group makes us think, there may be a weak relation between PON1 L 55 M polymorphism and AA.…”
Section: Discussionmentioning
confidence: 99%